Promotive and preventive interventions for mental health and well-being in adult populations: a systematic umbrella review - Saijonkari, Maija; Paronen, Elsa; Lakka, Timo; Tolmunen, Tommi; Linnosmaa, Ismo; Lammintakanen, Johanna; Isotalo, Jenni; Rekola, Hanna; Mäki-Opas, Tomi (Frontiers in Public Health, 2023)
Introduction Mental health disorders are increasing worldwide, leading to significant personal, economic, and social consequences. Mental health promotion and prevention have been the subject of many systematic reviews. Thus, decision makers likely face the problem of going through literature to find and utilize the best available evidence. Therefore, this systematic umbrella review aims to evaluate the effectiveness of interventions for promoting mental health and mental well-being, as well as for the primary prevention of mental health disorders. Methods Literature searches were performed in APA PsycInfo, Medline, and Proquest Social Science databases from January 2000 to December 2021. The search results were screened for eligibility using pre-defined criteria. The methodological quality of the included reviews was evaluated using the AMSTAR 2 tool. The key findings of the included reviews were narratively synthesized and reported with an emphasis on reviews achieving higher methodological quality. Results Out of the 240 articles found, 16 systematic reviews and four systematic umbrella reviews were included. The methodological quality of included reviews was low or critically low. Discussion This review suggests that interventions using cognitive-behavioral therapy and those developing resilience, mindfulness, or healthy lifestyles can be effective in the promotion of mental health and well-being in adult populations. Motivational interviewing may reduce alcohol consumption in young adults. Indicated or selective prevention is likely to be cost-effective compared to universal prevention. Parenting interventions and workplace interventions may be cost-effective in terms of promoting mental health. Due to the low methodological quality of the included reviews and substantial heterogeneity among the reported results, the findings from the reviews we summarized should be interpreted with caution. There is a need for further rigorous, high-quality systematic reviews.